Crafting the Patchwork: bricolage as an alternative for educational research - Marcos Garcia Neira; Bruno Gonçalves Lippi (Universidade Federal do Rio Grande do Sul, 2012)
The intensity of the current social changes has confronted the modernity legacy. The truths produced by the modern science have been under strong uncertainties. Even the way to produce knowledge is questioned nowadays. Amongst the emerging alternatives, there is the bricolage. The bricoleurs use a variety of methods, instruments and theoretical references that make possible to access and build interpretations fromvarious places. Driven by the Cultural Studies, denounce the relationship of power that influence the scientific speeches put in course. The present article discusses the presumptions and methodological procedures, and offers an example of educational research inspired in the bricolage.